White goods brand selection by using Generalized Choquet Integral - (:unkn) unknown (My University, 2013)
White goods brand selection decision have become a multi-criteria decision making problem depending on the variety of customer demands and developments at the white goods technology recently. In this study, the selection of the best among the alternative white goods brand is handled as a Multi Criteria Decision Making (MCDM) problem. Within the scope of this study, alternative three white goods brands (A, B, C) are evaluated. Firstly in the scope of the evaluation, a decision team is created as formed by two persons from three families who confronted with such kind of a choice problem. Common view of the decision team is taken for generating hierarchical decision model to be used in evaluation of alternative white goods brands. The Generalized Choquet Integral (GCI) method, being one of the MCDM methods, is used at solution of the problem. At the end of the study, obtained results and evaluations are included. © 2013 IEEE.
Keywords: generalized Choquet integral; white goods brand selection